Theoretical elements concerning the deprofessionalisation of Social Work - Hernández-Echegaray, Arantxa (Cuadernos de Trabajo Social, 2024)
Modern professions are a fundamental element in social organization. At the present time, the professions are experiencing a moment of transformation as a result of social changes, such as neoliberalism, bureaucracy, technocratization, the precariousness of contractual relationships and universal access to information. These changes are not alien to Social Work and represent a challenge for the profession both in its definition and in its social recognition. In addition, these changes delve into the problems of social identification and identity of Social Work. In this article, on the one hand, the main implications of the theory of de-professionalization are presented, and on the other, the implications of the civic paradigm, post-professionalization, and re-professionalization for Social Work and for the construction of a profession in line with the values, ethics and social essence of the profession, reducing the discomfort felt among its professionals.